Disproportionate impact of SARS-CoV-2 on ethnic minority and frontline healthcare workers: A cross-sectional seroprevalence survey at a North London hospital. Issue 6 (June 2021) - Martyn, Emily M.; Whitaker, Heather; Gil, Eliza; Ighomereho, Patricia; Lambe, Gerry; Conley, Ray; Saldiray, Janet; Ladhani, Shamez N.; Mirfenderesky, Mariyam
Highlights: Ethnic minority healthcare workers (HCW) had higher risk of seropositivity than White colleagues. Black African HCW were over twice as likely to have SARS-CoV-2 antibodies compared to White HCW. Emergency department and Covid-19 inpatient wards (non-AGP) staff had highest occupational risk. Highest seropositivity rates occurred in HCW living in more deprived areas local to the hospital.